State Awards as a Factor of Activation of the Donor Movement in Russia - A. V. Chistyakov (Управленческое консультирование)
The article is devoted to the problem of deficiency of donor blood and its components in the Russian Federation. The author points out the reasons that affect the willingness of citizens to participate in the donor movement and proposes solutions to improve the efficiency of donors activities. Including — in the sphere of social problems that are not directly related to the preparation of blood and its components due to the «activation» by the power structures of the unifying function of individual power symbols — state awards. The author also raises the question of amending the regulation on the Luka Krymsky medal and the statute of the Pirogov Order in order to increase the percentage of citizens of our country in the donor movement and their further involvement in social programs as donors and volunteers as part of their membership in the official order organization, the potential efficiency of which is confirmed by European practice.